IDENTIFICATION OF BROWN RUST TOLERANT AND DEVELOPMENT OF DISEASE TOLERANT HIGH YIELDING SPRING WHEAT (TRITICUM AESTIVUM L.) GENOTYPES - ULLAH , A; ISLAM , B; SAMAD , RA; GHUFFAR , S; AHMAD , K; SAEED , A; AHMAD , M; USMAN , U; NUSRAT , AT (Biological and Clinical Sciences Research Journal, 2024)
In the agricultural sector of Pakistan, wheat cultivation confronted a substantial obstacle in the form of leaf rust disease caused by the fungus Puccinia triticina. During the crop year 2021-22, a comprehensive screening was conducted on a hundred wheat genotypes to evaluate their resistance to this brown rust affliction. Results indicated six wheat genotypes tolerant to brown rust. Line into Tester mating design was used to assess combining ability. Grain yield and other related characters were studied in 18 F1 generations along with nine parents (six lines and three testers), which were evaluated for combining ability with three replications in a randomized complete block design (RCBD). The results indicated that among various lines, line 9479 was identified as a good general combiner for the character's spike length, spikelets per spike, and 1000-grain weight. In contrast, Line 9486 appeared as a good general combiner for the characters, flag leaf area, plant height, peduncle length, number of tillers per plant, and 1000-grain weight. Line 9515 is for flag leaf area, plant height, and spike length. Line 9519 for the number of tillers per plant, grain yield per plant, and plant height; line 9520 for peduncle length, number of tillers per plant, grains per spike, and grain yield per plant; and 9521 was identified as a good general combiner for the characters spike length, spikelet’s per spike, number of grains per spike and spike density. Tester Punjab-11 emerged as an excellent general combiner for the character's peduncle length, plant height, flag leaf area, and number of tillers per plant. In contrast, Tester Ass-11 appeared as a good combiner for the spike length, peduncle length, 1000-grain weight, and flag leaf area. Tester Chakwal-50 identified an excellent general combiner for the number of tillers per plant, plant height, grains per spike, spikelets per spike, grain yield per plant, 1000-grain weight, and spike density. Out of 18 cross combinations, seven crosses viz. 9479 × Aas-11, 9486 × Aas-11, 9515 × Aas-11, 9519 × Chakwal-50, 9520 × Punjab-11, 9521 × Punjab-11, and 9521 × Aas-11 emerged with significant positive SCA effects for grain yield per plant. Thus, a biparental mating system can exploit these crosses for grain yield per plant.